Isolation and characterization of lactic acid bacteria from fermented quinoa (Chenopodium quinoa) for use in vegetable biopreservation - SUNGEY NAYNEE SANCHEZ LLAGUNO; JEAN PIERRE MUÑOZ GUZMÁN; JUAN ALEJANDRO NEIRA MOSQUERA; JHONNATAN PLACIDO ALDAS MOREJON; KAROL YANNELA REVILLA ESCOBAR (Society for Indonesian Biodiversity, 2025)
Abstract. Llaguno-sungey NS, Muñoz Guzmán JP, Neira Mosquera JA, Aldas Morejon JP, Revilla Escobar KY. 2025. Isolation and characterization of lactic acid bacteria from fermented quinoa (Chenopodium quinoa) for use in vegetable biopreservation. Biodiversitas 26: 3174-3182. The objective of this study was to isolate and characterize Lactic Acid Bacteria (LAB) from fermented quinoa for biopreservation of broccoli (Brassica oleracea var. italica) and zucchini (Cucurbita pepo). A completely randomized design with bifactorial arrangement A×B was used, where factor A corresponded to the type of vegetable and factor B to the LAB concentration (1.0 × 10? and 2.0 × 10? CFU/mL). Analysis of the fermented musts showed a decrease in pH to 3.60 in white quinoa and 3.83 in red quinoa at 72 hours. Soluble solids also decreased to 8.2 and 8.6 °Brix, respectively. As for acidity, it was significantly higher in red quinoa (0.21%) compared to white quinoa (0.18%) at the end of fermentation. Lactococcus lactis subsp. lactis was identified as the predominant LAB (bootstrap of 92%). In the biopreservation application, broccoli treated with 2.0 × 10? CFU/mL showed a decrease in pH from 5.20 to 5.11, an increase in acidity from 0.19 to 0.23%, and soluble solids from 4.43 to 4.87 °Brix. For zucchini, pH decreased from 6.31 to 6.14, and acidity increased from 0.12 to 0.15%. Weight loss was greater in zucchini (from 0.42 to 0.82%) than in broccoli (from 0.31 to 1.46%). Microbiological analysis showed a reduction in mold and yeast counts in broccoli treated with 2.0 × 10³ CFU/mL at day 10. In terms of sensory analysis, zucchini received better ratings. In conclusion, fermented quinoa musts represent an effective source of LAB with biotechnological potential for vegetable preservation, highlighting their positive effect on physicochemical, microbiological, and sensory parameters, as well as their viability as a natural alternative for postharvest preservation.